Update of the H → WW () → eνμν analysis with 13.0 fb −1 of √ s = 8 TeV data collected with the ATLAS detector - Yoshihara, Keisuke (EPJ Web of conferences, 2013)
An update of the H → WW(*) → eνμν analysis has been performed with the ATLAS detector at the LHC. The analysis focuses on the mass region around 125 GeV where a discovery of a new neutral boson was made in 2012.